2016
DOI: 10.1055/s-0042-100193
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of acute upper gastrointestinal bleeding in relation to timing of endoscopy and the experience of endoscopist: a tertiary center experience

Abstract: Introduction: Patients with gastrointestinal bleeding admitted out of hours or at the weekends may have an excess mortality rate. The literature reports around this are conflicting. Aims and methods: We aimed to analyze the outcomes of emergency endoscopies performed out of hours and over the weekends in our center. We retrospectively analyzed data from April 2008 to June 2012. Results: A total of 507 ‘high risk’ emergency gastroscopies were carried out over the study period for various indications. Patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Five studies were carried out in Asia (Hong Kong, South Korea, Taiwan, and Saudi Arabia), 8 , 10–13 six in North America (USA), 4 , 6, 14–17 and nine in Europe (Italy, the Netherlands, Serbia, and the United Kingdom) 2 , 3, 5, 7, 18–22 . Six studies reported patients with UGIH caused by peptic ulcer, 8 , 10, 12, 19, 20, 22 one study included patients with bleeding gastroduodenal angiodysplasia, 17 three demonstrated the sources of bleeding were from the esophagus varix, 11 , 13, 15 and 10 studies included patients with both variceal and nonvariceal UGIH 2 , 3, 5–7 , 14, 16, 18, 21, 22 . Most recruited studies defined the “off‐hours” as weekends only,4–7, 11, 13–17 , 21 while four studies defined it as weekends and public holidays; 3 , 8, 12, 18 one study defined it as weekends and nighttime, 20 and one study defined it as nighttime only 19 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Five studies were carried out in Asia (Hong Kong, South Korea, Taiwan, and Saudi Arabia), 8 , 10–13 six in North America (USA), 4 , 6, 14–17 and nine in Europe (Italy, the Netherlands, Serbia, and the United Kingdom) 2 , 3, 5, 7, 18–22 . Six studies reported patients with UGIH caused by peptic ulcer, 8 , 10, 12, 19, 20, 22 one study included patients with bleeding gastroduodenal angiodysplasia, 17 three demonstrated the sources of bleeding were from the esophagus varix, 11 , 13, 15 and 10 studies included patients with both variceal and nonvariceal UGIH 2 , 3, 5–7 , 14, 16, 18, 21, 22 . Most recruited studies defined the “off‐hours” as weekends only,4–7, 11, 13–17 , 21 while four studies defined it as weekends and public holidays; 3 , 8, 12, 18 one study defined it as weekends and nighttime, 20 and one study defined it as nighttime only 19 .…”
Section: Resultsmentioning
confidence: 99%
“…Mortality was in-hospital in all studies in North America, whereas 30-day mortality was reported in some studies in Asia 8,12 and Europe. 2,3,7,[19][20][21][22] Thirty-day mortality includes all-cause deaths occurring only within 30 days of hospitalization and after being discharged from the hospital. For in-hospital mortality, all mortality will be counted, so long as the patient stays in the hospital.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations